2019
DOI: 10.3390/en12112106
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Effects of Arms with Different Cross-Sections on Straight-Bladed Vertical Axis Wind Turbine

Abstract: Most vertical axis wind turbines (VAWTs) need arms connecting the blades with the rotational axis. The arms increase the power loss of VAWTs; however, the distribution between the pressure and friction influences and their degrees of influence have not yet been investigated in detail in past research. We applied computational fluid dynamics (CFD) targeting a small-sized straight-bladed VAWT to elucidate the effects of arms on turbine performance. In the analysis, three kinds of arms with different cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This same conclusion is approached in reference [15]. Hara Y et al studied the influence of arms of different sections on the VAWT and found that the drag torque of the rotor of the airfoil arm added to the blade became larger than that of other arms [16].…”
Section: Introductionsupporting
confidence: 58%
“…This same conclusion is approached in reference [15]. Hara Y et al studied the influence of arms of different sections on the VAWT and found that the drag torque of the rotor of the airfoil arm added to the blade became larger than that of other arms [16].…”
Section: Introductionsupporting
confidence: 58%
“…Many studies have been done on the VAWT to optimize or maximize its performance way by suggesting and comparing various different types of turbine blades. Comparisons between support arm geometries such as implementing symmetrical NACA blades [5,6] or variations of it [7,8] as well as other shapes [9,10] which generally tends to favour airfoils shapes when it comes to power efficiency losses. However, implementation of shape optimization techniques to generate a novel blade design for VAWT use has recently seen a rise in interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Benjamin Strom et al (Strom et al, 2018) introduced the analytical models for the power loss due to mounting structure drag and examined the interactions between turbine blades and mounting structures. Yutaka Hara et al (Hara et al, 2019) attached three types of support arms with different cross-sectional shapes to a small SB-VAWT rotor without support arms. The surface pressure and friction distribution on the blades and support arms were analyzed using CFD.…”
Section: Figurementioning
confidence: 99%